Natural History and Risk Factors of Infantile Atopic Dermatitis: A Case Report and Literature Review - Christopher, Paulus Mario; Hung, Maggie Stella (Medicinus, 2020)
Atopic dermatitis (AD) or atopic eczema is one of the most common forms of pediatric dermatological skin conditions, primarily beginning in childhood with a variable natural course characterized by intense pruritus and eczematous lesions. This condition requires multifactorial interplay and risk factors to explain the pathogenesis. We hereby report a case of a two-month-old male who presented with widespread erythematous lesions, excoriations, and dry skin since one day before admission. The antenatal history showed use of antibiotics during pregnancy, familial history of atopy, and non-exclusive breastfeeding which are all known risk factors. Dermatological examination revealed skin phototype III with diffuse erythematous patches scattered on the face, trunk, upper and lower limbs, and groin followed with excoriations and palmar hyperlinearity. Further laboratory and histopathological examinations were not conducted. The patient was treated with topical corticosteroid and emollients, resulting in a notable improvement without any further flares. A thorough history taking and physical examination must be conducted to establish the diagnosis based on the Hanifin and Rajka criteria and identify risk factors such as genetic factors, impaired skin barrier, and environmental factors and microbial exposure, which may play a protective or harmful role in AD development. Holistic treatments consist of pharmacological and non-pharmacological treatments, with significant emphasis on education to the patient and caregiver(s) to improve quality of life and prevent exacerbations and infectious complications while minimizing potential medication side effects.